Respuesta :

Answer:

B. equivalent

Step-by-step explanation:

Our two equations are:

[tex]y=-\frac{1}{3} x +\frac{2}{3}[/tex]

[tex]2x+6y=4[/tex]

Let's use substitution and plug in the expression [tex]-\frac{1}{3} x +\frac{2}{3}[/tex] for y in the second equation. That way, we're getting rid of a variable so we can solve for the other:

[tex]2x+6y=4[/tex]

[tex]2x+6(-\frac{1}{3} x +\frac{2}{3})=4[/tex]

[tex]2x-2x+4=4[/tex]

[tex]4=4[/tex]

[tex]0=0[/tex]

This means that there are an infinite number of solutions possible for this system - any x value will work. So, the answer is equivalent, because these two equations are essentially the same.

Answer:

Dependent

Step-by-step explanation:

y = -⅓x + ⅔

Multiply by 3

3y = -x + 2

x + 3y = 2

Multiply by 2

2x + 6y = 4

Same as equation 2

When a system consists of equations of the same line written in different forms, it's called a dependent system